Increased Risk of Dementia in Patients With Acute Organophosphate and Carbamate Poisoning. Issue 29 (July 2015) - Lin, Jiun-Nong; Lin, Cheng-Li; Lin, Ming-Chia; Lai, Chung-Hsu; Lin, Hsi-Hsun; Yang, Chih-Hui; Kao, Chia-Hung; Marco, Onofrj.
<x xml:space="preserve">Abstract</x> Abstract Organophosphate (OP) and carbamate (CM) are the most commonly used pesticides against insects. Little is known regarding the relationship between dementia and acute OP and CM poisoning. A nationwide population-based cohort study was conducted from the National Health Insurance Research Database in Taiwan. The incidence and relative risk of dementia were assessed in patients hospitalized for acute OP and CM poisoning from 2000 to 2011. The comparison cohort was matched with the poisoned cohort at a 4:1 ratio based on age, sex, and the year of hospitalization. During the follow-up period, the incidence of dementia was 29.4 per 10, 000 person-years in the poisoned group, and represented a 1.98-fold increased risk of dementia compared with the control cohort (95% confidence interval, 1.59–2.47). This study provides evidence on the association between dementia and acute OP and CM poisoning. Regular follow-up of poisoned patients for dementia is suggested.